2010
DOI: 10.1117/12.851307
|View full text |Cite
|
Sign up to set email alerts
|

Performance and comfort of monocular head-mounted displays in flight simulators

Abstract: One of our previous studies examining the integration of a head-mounted visual display with a faceted flight simulator display showed that a monocular condition was the most uncomfortable and it also resulted in poorer operator performance. In the present study, we investigated whether this reduction in performance was dependent on eye dominance and whether it could be reduced or eliminated through training. Our performance measure was the amount of time it took operators to make correct decisions on a simplif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…As Brown et al [ 7 ] have suggested, we compared the impact of the display eye according to binocular background conditions. Our results suggest that the impact of the display eye on performance does not depend on the binocular background conditions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As Brown et al [ 7 ] have suggested, we compared the impact of the display eye according to binocular background conditions. Our results suggest that the impact of the display eye on performance does not depend on the binocular background conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Performance and comfort were also evaluated with different binocular background contrasts. While previous studies have only varied the contrast of the monocular element [ 6 , 7 , 35 ], our study compared the impact of contrast variation of the binocular background on interocular conflict. Our findings show that, regardless of the contrast of the monocular element, tracking performance was better in the LFS-100% condition than in LFS-20% condition (see Fig 10A ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations